The quality of teachers: training, recruitment, career advancement. What scenario? - Trinchero, Roberto; Calvani, Antonio; Marzano, Antonio; Vivanet, Giuliano (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2020)
Beyond the specific conditions induced by the health emergency in our country, it is now clear that the school presents itself in a“structural”emergency condition. The situation requires organic and courageous interventions starting from what represents the recognized fulcrum of the school system: the quality of teachers. The article proposes an answer to the complicated (and urgent) question of initial training and entry into teaching for secondary school teachers. After a brief review of the current weaknesses of the Italian school and of the legislative initiatives that have been advanced, modified and replaced in the last twenty years, an overall solution is proposed for a training course progressively oriented towards increasingly advanced expertise levels, which allows also to address the problem of recruitment and career advancement. The premise is a different conception of the training, which focuses the attention on the real school problems, with an indication of effective, reliable and sustainable ways to face them, in opposition to the abstract, cumulative and transmissive traditional model.